A Comparison Of The Performances Of Various Single Variable Charts. - A. Atta, Abdu. M.; B, Michael . C. Khoo; S, K. Lim (2009)
Control charts are used for process monitoring and improvement in industries. Two charts are usually used in the monitoring of both the mean and variance separately.